The Rhetoric of Jesus in the Gospel of Mark - Young, David M. (Minister); Strickland, Michael, 1974- (Book collections on Project MUSE., 2018)
Young and Strickland analyze the four largest discourses of Jesus in Mark in the context of Greco-Roman rhetoric in an attempt to hear them as a first-century audience would have heard them. Their analysis uncovers how the discourses are constructed; what issues each discourse seeks to treat; how the argumentation, arrangement, and style of each discourse contributes to its overall purpose; and how the discourse fits into the overall narrative context of the Gospel. The authors demonstrate that, contrary to what some historical critics have suggested, first-century audiences of Mark would have found the discourses of Jesus unified, well-integrated, and persuasive. They also show how these speeches of the Markan Jesus contribute to Mark's overall narrative accomplishments.